Ответ:
Пошаговое объяснение:
З) (3/7)^2=9/49
9/49+5/7=9/49+35/49=44/49
7/11*44/49=4/7
К)4/5+1/6=24/30+5/30=29/30
23 2/3-15 5/9=23 6/9-15 5/9=8 1/9
29/30*8 1/9=29/30*73/9=2117/270
2117/270*45/58=2117/348=6 29/348
6 29/348-1/2=6 29/348-174/348=
5 203/348=5 7/12
Скорее всего так: к - с
Просто если стоит к, значит что оно больше чем с потому что стоит в начале :)
0,456; 0,079; 0,065; 0.0502; 0,0093; 0,009
<span>(tg a +ctg a)(1+cos a)(1-cos a ) = (Sin</span>α/Cosα + Cosα/Sinα)(1 - Cos²α)=
=(Sin²α + Cos²α)/SinαCosα * Sin²α = 1/Cosα * Sinα = Sinα/Cosα = tgα
1)500-180:(90:45)+30=190
2)(90+510:30)*(80:4*5)=10700